2013
DOI: 10.4236/as.2013.412089
|View full text |Cite
|
Sign up to set email alerts
|

The role of seed priming in improving seedling growth of maize (<i>Zea mays</i> L.) under salt stress at field conditions

Abstract: Salinity is considered as a major abiotic stress affecting germination, seedling growth and crop production in arid and semi-arid regions. Many techniques are used to improve tolerance to salinity. Priming is believed to be an effective solution that increases germination, plant growth and improve yield of several vegetables and crops under saline soil condition. The objective of this study was to see the effect of seed priming with 5 g/L NaCl on maize seedling growth exposed to five salinity levels under fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Fresh and dry weights of roots and shoots were increased. Under salt stress, seed priming lessened the inhibitory effect of salt stress on maize seedling growth [125]. Priming with NaCl also increased plant height and yield and induced early emergence, more germination rate, more shoot length and dry weight, and more leaf chlorophyll, area, and number [126].…”
Section: Seed Primingmentioning
confidence: 96%
“…Fresh and dry weights of roots and shoots were increased. Under salt stress, seed priming lessened the inhibitory effect of salt stress on maize seedling growth [125]. Priming with NaCl also increased plant height and yield and induced early emergence, more germination rate, more shoot length and dry weight, and more leaf chlorophyll, area, and number [126].…”
Section: Seed Primingmentioning
confidence: 96%
“…Similarly, [13] and [20] showed increased germination as well as growth parameters in Tunisian coriander seeds primed with NaCl and CaCl2 and safflower (Carthamus tinctorius) seeds primed with NaCl and KCl respectively compared with unprimed seeds. Again, it is seen that [21] reported that treating maize seeds with NaCl and sowing under normal and saline conditions improved performance of maize plants under field and laboratory conditions. It is known that salinity adversely affects plants by reducing root growth, leaves and dry weight of aerial parts as it interferes in phytohormone biosynthesis, its mode of action, which ultimately reduces photosynthesis and overall plant production and biomass.…”
Section: Halo-primingmentioning
confidence: 97%
“…Saline soils occupy 7% of the earths land surface and increased salinization of arable land will result into 50% land loss by the middle of the 21st century (Ahanger et al, 2017). Under salt stress, important processes such as lipid metabolism, protein synthesis and photosynthetic capacity are distorted subsequently results in poor seed germination and plant growth (Abraha and Yohannes, 2013). Salt stress deteriorate chlorophyll contents, nitrate contents, inhibit carbonic anhydrase, nitrate reductase, net phtotosynthetic rate, stomatal conductance, PSII reaction centre, disrupt electron transport in the photosynthetic apparatus, induced ion imbalance along with disturbed membrane integrity and water relations (Flowers and Colmer, 2015).…”
Section: Introductionmentioning
confidence: 99%